Age at Parkinson's disease onset modulates the effect of levodopa on response inhibition: Support for the dopamine overdose hypothesis from the antisaccade task. (10th December 2021) - Waldthaler, Josefine; Stock, Lena; Krüger-Zechlin, Charlotte; Timmermann, Lars
Abstract: The antisaccade task is an established eye-tracking paradigm to explore response inhibition. While many studies showed that antisaccade performance is impaired in Parkinson's disease (PD), the effect of dopaminergic medication is still an area of debate. According to the dopamine overdose hypothesis, intrinsic basal dopamine levels in ventral parts of the striatum determine whether levodopa intake has beneficial or detrimental effects on dopamine-dependent cognitive tasks. The objective of this study was therefore to explore the effect of several disease-related factors on changes in antisaccade performance after levodopa intake in PD. Thirty-five individuals with PD (and 30 healthy controls) performed antisaccades in OFF and ON medication state. Multiple linear regressions were calculated to predict the change in antisaccade latency, directive errors and express saccade rate based on age at PD onset, disease duration, levodopa-equivalent daily dose, motor symptom severity and executive functions. Levodopa intake did not alter antisaccade performance on a group level. However, the effect of levodopa was differentially modulated by age at PD onset and motor symptom severity. Earlier disease onset and milder motor symptoms in OFF medication state were associated with reduced response inhibition capacity after levodopa intake measured as increased express saccade and error rates. Our results indicate that levodopa may have opposing effects on oculomotor response inhibition dependent on the age at PD onset and motor disease severity. Assuming less dopaminergic loss in ventral parts of the striatum in early compared to late onset PD, these findings support the dopamine overdose hypothesis. Highlights: Effect of dopaminergic medication on antisaccades modulated by age at PD onset. Younger age at onset associated with larger increase of express saccades and errors ON – OFF. Impaired proactive response inhibition in early-onset PD after levodopa. Supportive of dopamine overdose in the caudate nucleus in early-onset PD.